Daulat raja menuju daulat rakyat : demokratisasi pemerintahan Yogyakarta / Tri Yuniyanto ; editor, Kundharu Saddhono, Yogyo S. Yono. - TRI YUNIYANTO; Kundharu Saddhono (Cakra Books, 2010)
xii, 133 hlm. ; 21 cm (3 eks.)